Formulasi Terhadap Sistematika Akta Dalam Akad Syariah Yang Berkepastian Hukum - Ady Setyo Fardiyanto (Lex Renaissance, 2021)
This study aims to describe and analyze the juridical implications of the validity of the deed made by the Notary related to the addition of the Qur'anic verse, as well as the formulation of the systematic deed in the sharia contract with legal certainty. The type of research used is empirical juridical research. The approach used is statutory and a case approaches, with qualitative descriptive analysis. The results of this study conclude that first, the use of such verses of the Qur'an does not violate the provisions of the legislation if it is placed at the beginning of the contents of the deed or at the end of the premise. That the beginning and end of the deed is absolutely the responsibility of the Notary. However, the content of the deed is a written agreement desired by the parties. As long as it is based on the applicable laws and regulations. Second, the making of sharia banking deeds made in the form of a notary deed must be made in the form of a notary deed in accordance with the formalities of a notary deed as regulated in Article 38 of the Notary Position Act. If there are procedures that are not fulfilled, the deed with a court process can be declared as a deed that has the power of proof under the hand. If the parties or clients request to add verses of the Qur'an to the notary deed, it is necessary to pay attention to the notary in placing the verse so that it does not violate the provisions of Article 38 of the Notary Position Act.Key Words: Notary deed; notary office law; sharia banking deedAbstrakPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis mengenai implikasi yuridis terhadap keabsahan akta yang dibuat oleh Notaris terkait dengan penambahan ayat al-Qur’an, serta formulasi mengenai sistematika akta dalam akad syariah yang berkepastian hukum. Jenis penelitian yang digunakan adalah penelitian yuridis empiris. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan kasus, dengan analisis deskriptif kualitatif. Hasil penelitian ini menyimpulkan, pertama, penggunaan ayat-ayat al-Qur’an demikian tidak melanggar ketentuan perundang-undangan apabila diletakkan pada awal isi akta atau pada akhir premisse. Bahwa awal dan akhir akta mutlak merupakan tanggungjawab Notaris. Namun untuk isi akta merupakan kesepakatan tertulis yang dikehendaki oleh para pihak. Sepanjang berdasarkan peraturan perundang-undangan yang berlaku. Kedua, pembuatan akta-akta perbankan syariah yang dibuat dalam bentuk akta Notaris harus dibuat dalam bentuk akta Notaris sesuai dengan formalitas akta Notaris yang diatur dalam Pasal 38 Undang-Undang Jabatan Notaris. Apabila ada prosedur yang tidak dipenuhi, akta tersebut dengan proses pengadilan dapat dinyatakan sebagai akta yang mempunyai kekuatan pembuktian di bawah tangan. Apabila para pihak atau klien meminta untuk ditambahkannya ayat al-Qur’an ke dalam akta Notaris maka perlu diperhatikan oleh Notaris di dalam penempatan ayat tersebut supaya tidak menyalahi ketentuan Pasal 38 Undang-Undang Jabatan Notaris.Kata Kunci: Akta notaris; akta perbankan syariah; undang-undang jabatan notaris